Identification of an unknown person using Y-chromosome markers and mitochondrial dna typing - Krivda, Ruslan G.; Jassim, Aymen A.; Fernandez Trokhimtchouk, Tatiana B. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: The present article is concerned within the scope of Forensic Medicine, specifically Forensic Genetics. The case was taken care of in the Genetic-Molecular Laboratory of the Odessa Regional Bureau of Forensic-Medical Examinations, in Ukraine, during January and February of 2014.Objectives: The aim of our work was to identify an unknown person, using the techniques: Y-chromosome markers and mitochondrial DNA typing.Materials and methods: The materials available for our procedure were: pieces of tissue in paraffin blocks, saved from the corpse of the unknown person; blood from a living male subject, who claimed to be the grandfather, and from two females, allegedly the sisters. From all of them we extracted nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) respectively, that was analyzed to compare and draw the proper conclusions.Results: The analyzed genetic materials confirmed the kinship.Conclusion: Using Y-chromosome markers we were able to establish the correspondence of the subject to his paternal line, and by mitochondrial DNA typing we could establish his relation to the proper maternal line.